Habitats, phytochemical metabolites and phytoremediation potential of Ranunculus sceleratus L. - Khalifa , Salem Mousbah; Badr, Badr Mohamed (Journal of Pure & Applied Sciences, 2021)
Ranunculus sceleratus L. (Ranunculaceae) is an invasive alien widespread species commonly distributed in canals and drains banks. In Egypt, this plant exhibits extensive growth with occasional pure populations in the Nile Delta region. This study aimed to address the drivers for R. sceleratus abundance, phytochemical composition, and phytoremediation efficiency. The average abundance of R. sceleratus within 60 stands of 25 m2 each was 47.9. The average root and stem lengths were 31.5 and 60.1 cm, respectively. The abundance of R. sceleratus was positively correlated with pH, electric conductivity, organic carbon, Fe, Mn, and Zn, while negatively correlated with total dissolved phosphorus, Cu, Co, Cd, and Pb. The shoot had the highest values of all bioactive-metabolites, where phenols, flavonoids, tannins, alkaloids and saponins were recorded 23.16, 5.11, 14.78, 6.34 and 18.50 mg kg-1 dry weight, respectively. R. sceleratus had shoot and root bioaccumulation factors (BF) in the following orders: Cd> Ni> Cu> Pb> Zn> Fe> Mn> Co. R. sceleratus had BFshoot value of more than one for Ni, Cu, and Pb, while BFroot was greater than one for Cd, Ni, Cu, Pb, Zn, and Fe. Nevertheless, the translocation factor (TF) for all heavy metals were lower than one. Accordingly, R. sceleratus is a candidate for phytostabilization and/or phytoextraction tool for the most investigated heavy metals.